Karakteristik Penderita TB Paru pada Tahun 2018-2021 di RSUD Arifin Achmad Provinsi Riau - Isnaniar; Norlita, Wiwik; Isza, Mervillo (As-Shiha: Jurnal Kesehatan, 2022)
The high incidence of TB in Indonesia has the potential for TB patients, which in turn can lead to an increase in TB cases. Tuberculosis can be suffered by various ages from children to adults. TB germs are transmitted through the air, and can be inhaled by other people around them. Objective: To find out the Characteristics of Pulmonary TB Patients in 2018 to 2021 at Arifin Achmad Hospital, Riau Province. Methods: This type of research is descriptive. This research was conducted from 01 to 12 August 2022 at Arifin Achmad Hospital, Riau Province, Pekanbaru City. The sample in this study amounted to 456 people. Purposive Sampling Technique. The instrument used in this study was a checklist sheet obtained through the medical records of pulmonary TB patients who were registered at the Arifin Achmad Hospital, Riau Province from 2018 to 2021.Results: The most affected by pulmonary TB were the age of 46 - 55 years 64 people (39.0 %) in 2021, the sex of the highest pulmonary TB sufferer - male is 115 people (70.1%) in 2021, from the history of contact with TB patients it was found that more were 146 people (89.0%) in 2021, and those who have a history of contact with TB patients are 143 people (87.2%) in 2021. From the immunization status the most are those who have received BCG immunization, namely 146 people (89.0%) in 2021. Conclusion: In this study, most experienced pulmonary TB were men, with the highest age being 26-35 years old, and negative BCG immunization with more people who did not get a history of TB contact with other patients